Enhancing Second-Language Learners’ Pragmatic Competence: Underlying the Performance of Speech Acts - Nadhreen, Basim (European Scientific Journal, ESJ, 2026)
This study draws attention to a growing area of interest in second language acquisition research, especially pragmatic ability. It focuses on a subfield of pragmatics known as speech acts and examines the mechanisms that underpin their execution. The researcher used a test as an instrument for data collection. The results of this test reveal that the respondents’ answers were semi- native patterns close in comparison to those of the native speakers, who also have varied ones. It has been observed that students resort to their own cultural norms because of their imperfect knowledge of the target culture. In other words, they have little knowledge of what expressions to use in what situations. The students need to know how and when politeness strategies are realized appropriately in L2. The findings mentioned above call for an urgent need to reconsider the teaching of speaking skills at the university. If one of the main objectives of any English program is to make learners effective communicators, it is necessary to build up a syllabus. including pragmatic aspects with the aim of developing learners’ pragmatic competence.